Fantastic failures : true stories of people who changed the world by falling down first - Reynolds, Luke (Aladdin ; Beyond Words, 2018)
"There is a lot of pressure in today's society for kids to succeed, but failing is a part of learning how to be a successful person. In his teaching career, Luke Reynolds saw the stress and anxiety his students suffered over grades, fitting in, and getting things right the first time. Fantastic Failures was created for these students to learn that their mistakes and failures do not define their whole lives, but help them grow into their potential. Kids will love learning about some of the well-known people who failed before succeeding and will come to understand that failure is a large component of success. With stories from people like J.K. Rowling, Albert Einstein, Rosa Parks, Abraham Lincoln, Vincent Van Gogh, Julia Child, and Steven Spielberg, each profile just proves that the greatest mistakes and flops can turn into something amazing. Intermixed throughout the fun profiles, Reynolds spotlights great inventors and scientists who discovered and created some of the most important medicines, devices, and concepts of all time, including lifesaving vacines and medicines that were stumbled upon by mistake. Reynolds's engaging, youthful voice pulls kids into each anecdote much in the same way bestselling Girls Who Rocked the World and Boys Who Rocked the World do, making the teaching moments feel more like a friend just retelling a story. Each profile is followed up with advice on how to come back from your own flops and move forward to succeed"--